Plan de Marketing para Impulsar los Atractivos Turísticos Naturales y Gastronomía Típica de la parroquia Timbara, del Cantón Zamora, Provincia de Zamora Chinchipe, 2015 - Ontaneda Salinas, Jeisson Jael (2016)
This paper begins by describing the tourist reality of the parish Timbara Canton Zamora, Zamora Chinchipe, due to the large number of natural and gastronomic attractions it holds. This research was conducted in order to raise a proposed Plan of Tourist Marketing of natural sites and gastronomy of the Timbara parish, in order to be considered to enable this activity in the parish, under the principles of sustainability necessary tour. For the development of the Marketing Plan as an overall objective raised: Develop a Marketing Plan to boost tourist natural sites and gastronomy of the Canton parish Timbara Zamora, also three specific objectives; A diagnosis of the current situation of natural sites and determine its main existing needs; designing the proposed advertising and promotion of natural and gastronomy sites; socialize the proposed marketing authorities Timbara parish. To fulfill the objectives of the methodology used in the study, covering targeted surveys of tourists, merchants, analysis of the tourism situation by observing the supply, demand, competition analysis and review of information from books was raised , magazines, websites and interviews and consultations with the people involved, the technique of SWOT strengths, weaknesses, opportunities and threats was applied, and field visits were made to places where recreational and nature centers are located in the in order to observe the state they are in and the services offered. With the results obtained a marketing plan for the promotion and dissemination at the local level, using means such as leaflets, radio spots, advertising shirts, hats, cards arises. In conclusion Timbara parish has great natural attractions and varied cuisine offered by its inhabitants, are considered to be source of tourist wealth, which should be exploited. The Timbara parish lacks a tourist information center therefore has no guidelines, policies and strategies to guide their activities and enabling them to optimize and make better use of existing natural attractions, these being a key pillar generation resources that benefit the population of the parish Timbara. Today the parish has not made tourism training to help with its development. It determined that the main weakness of the study area is the poor promotion and vision of the people of the community, to the use of natural resources considered as tourism, the Autonomous Government Decentralized recommended the Timbara parish to encourage and optimize the tourist use areas of the parish, through the creation of investment projects, sources of information and tourism promotion, as well as improve signaling within the parish, always ensuring that these operations generate the least environmental impact. It is suggested to the parish register GAD Timbara the National Tourism Training Plan Request free training that are aimed at people involved in the tourism industry.